2018
DOI: 10.1007/s10120-018-0833-y
|View full text |Cite
|
Sign up to set email alerts
|

PODXL, negatively regulated by KLF4, promotes the EMT and metastasis and serves as a novel prognostic indicator of gastric cancer

Abstract: KLF4/PODXL signaling pathway assumes an irreplaceable role in tumorigenesis, invasion and metastasis of human GC and PODXL serves as an independent prognostic indicator for GC patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 33 publications
0
42
1
Order By: Relevance
“…Accordingly, forced expression of PODXL in A549 cells promoted changes characteristic of EMT through a process dependent on the activation of PI3K/AKT signaling pathway [87]. Similarly, PODXL silencing in HCT15 colon cancer cells and in SGC-7901 and AGS gastric cancer cells led to a reduction of EMT-associated markers [51,54]. Moreover, the analysis of mRNA expression levels in patients with colon cancer using GSE17536 datasets revealed a positive correlation of PODXL expression with the mesenchymal markers vimentin, N-cadherin, TWIST2, SLUG, and ZEB1 and a negative correlation with the epithelial marker E-cadherin [54].…”
Section: Podxl In Emtmentioning
confidence: 92%
See 3 more Smart Citations
“…Accordingly, forced expression of PODXL in A549 cells promoted changes characteristic of EMT through a process dependent on the activation of PI3K/AKT signaling pathway [87]. Similarly, PODXL silencing in HCT15 colon cancer cells and in SGC-7901 and AGS gastric cancer cells led to a reduction of EMT-associated markers [51,54]. Moreover, the analysis of mRNA expression levels in patients with colon cancer using GSE17536 datasets revealed a positive correlation of PODXL expression with the mesenchymal markers vimentin, N-cadherin, TWIST2, SLUG, and ZEB1 and a negative correlation with the epithelial marker E-cadherin [54].…”
Section: Podxl In Emtmentioning
confidence: 92%
“…On the other hand, PODXL overexpression in MCF-7 breast cancer cell line stimulated invadopodia formation and activation, through the induction of Rac1/Cdc42/cortactin signaling [82]. The migratory and invasive properties promoted by PODXL has also been demonstrated in vitro in colorectal cancer (HCT116, LOVO and HCT15), gastric cancer (SGC-7901, AGS, BGC823, and MGC803), malignant testicular tumor (NT2), oral squamous cell carcinoma (SAS), lung adenocarcinoma (A549), and glioblastoma multiforme (LN-299 and U-118) cell lines [32,46,51,54,[75][76][77][78]87]. Besides, silencing of PODXL in both NAMEC8R and the highly metastatic MDA-MB-231 4175 breast cancer cells decreased extravasation in vitro, an effect which was totally reversed by overexpressing wild type PODXL [81].…”
Section: Podxl In Metastasismentioning
confidence: 95%
See 2 more Smart Citations
“…Krüppel‐like factor 4 played a negative role in gastric cancer cell invasion, which was reversed by upregulation of serine/threonine kinase 33 expression at the transcriptional level 20 . Our previous studies found that loss of KLF4 expression contributed to enhance human gastric cancer EMT and metastasis development and progression through regulating PODXL 21 . However, the underlying molecular mechanism of the tumor‐suppressive role of KLF4 in CRC is still vague, and needs to be further investigated.…”
Section: Introductionmentioning
confidence: 91%